Shanghai coastal reservoirs: Their development and experience from their design - Yuan, Jian Zhong (IAHR, 2020)
Shanghai has three coastal reservoirs used for drinking water sources in the Yangtze estuary. They are the Qingcaosha reservoir, the Dongfengxisha reservoir and the Chenhang reservoir. This article discusses why Shanghai needed to build coastal reservoirs and their evolution. The characteristics of the Shanghai drinking water sources are introduced. The key factors and the experience gained from the research and design of the Shanghai coastal reservoirs have been summarized and explained.